FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN MENGAJAR MAHASISWA PPL PGSD FKIP UNSYIAH DI SEKOLAH LATIHAN - Alfiati Syafrina (JURNAL FISIKA EDUKASI, 2015)
This study aims to find out the factors that affect the ability of the student teaching Practice Field Experience Elementary Teacher Education the Faculty of Teacher Training and Education on training school. The study population is a student majoring in Practice Field Experience Elementary Teacher Education the Faculty of Teacher Training and Education Syiah Kuala University academic year 2013/2014 which is implementing Practice Field Experience in SD Negeri Kota Banda Aceh total of 106 person. The sample is 15% of the total population is 19 people. The research data captured through documentation and questionnaires. Analysis of descriptive data. The results of data analysis is can be concluded that the factors that affect the ability of the student teaching Practice Field Experience Elementary Teacher Education the Faculty of Teacher Training and Education on the teacher-training school that officials in the activities: preparation of teaching, teacher observation by officials in class, feedback and assessment for learning in the classroom, suggestions for improvement each finished teaching, preparation of media, the opportunity to practice teaching in class, master the subject matter, classroom management, and implementation and management evaluation.